1982
DOI: 10.1111/j.1469-8986.1982.tb02552.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Neonatal Blood Pressure: A New Method

Abstract: Psychophysiological research on the neonatal cardiac system has focused almost exclusively on heart rate. Other cardiovascular parameters such as blood pressure (BP) have been difficult, if not impossible, to examine in the newborn due to the difficulty involved in measurement. This study tested a new, non‐invasive device that simultaneously measured systolic, diastolic, and mean arterial BP and heart rate in the newborn. Eighty healthy babies’ BP and heart rate were measured for the first 3 days of life and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Oscillometric determination of blood pressure (BP) in critically ill newborns is an accepted method for non-invasive BP (NIBP) measurement (1)(2)(3). Extensive studies have shown excellent correlation between direct and oscillometric BP measurement ( 2 4 ) .…”
mentioning
confidence: 99%
“…Oscillometric determination of blood pressure (BP) in critically ill newborns is an accepted method for non-invasive BP (NIBP) measurement (1)(2)(3). Extensive studies have shown excellent correlation between direct and oscillometric BP measurement ( 2 4 ) .…”
mentioning
confidence: 99%